Protocetraric and Salazinic Acids as Potential Inhibitors of SARS-CoV-2 3CL Protease: Biochemical, Cytotoxic, and Computational Characterization of Depsidones as Slow-Binding Inactivators - Lorenza Fagnani; Lisaurora Nazzicone; Pierangelo Bellio; Nicola Franceschini; Donatella Tondi; Andrea Verri; Sabrina Petricca; Roberto Iorio; Gianfranco Amicosante; Mariagrazia Perilli; Giuseppe Celenza (MDPI AG, 2022)
The study investigated the inhibitory activity of protocetraric and salazinic acids against SARS-CoV-2 3CLpro. The kinetic parameters were determined by microtiter plate-reading fluorimeter using a fluorogenic substrate. The cytotoxic activity was tested on murine Sertoli TM4 cells. In silico analysis was performed to ascertain the nature of the binding with the 3CLpro. The compounds are slow-binding inactivators of 3CLpro with a Ki of 3.95 μM and 3.77 μM for protocetraric and salazinic acid, respectively, and inhibitory efficiency kinact/Ki at about 3 × 10−5 s−1µM−1. The mechanism of inhibition shows that both compounds act as competitive inhibitors with the formation of a stable covalent adduct. The viability assay on epithelial cells revealed that none of them shows cytotoxicity up to 80 μM, which is well below the Ki values. By molecular modelling, we predicted that the catalytic Cys145 makes a nucleophilic attack on the carbonyl carbon of the cyclic ester common to both inhibitors, forming a stably acyl-enzyme complex. The computational and kinetic analyses confirm the formation of a stable acyl-enzyme complex with 3CLpro. The results obtained enrich the knowledge of the already numerous biological activities exhibited by lichen secondary metabolites, paving the way for developing promising scaffolds for the design of cysteine enzyme inhibitors.